Syndrome of symptomatic adult acetabular dysplasia (SAAD syndrome). Issue 4 (1st April 2003) - Birrell, F; Silman, A; Croft, P; Cooper, C; Hosie, G; Macfarlane, G
Abstract : Objectives: To determine the prevalence of acetabular dysplasia in subjects presenting with hip pain to primary care and its relationship with radiographic osteoarthritis (OA) of the hip. Design: Cross sectional analysis of a prospective cohort. Setting: 35 general practices across the UK. Subjects: 195 patients (63 male, 132 female) aged 40 years and over presenting with a new episode of hip pain Results: The prevalence of acetabular dysplasia in this study of new presenters with hip pain was high (32%). There was no significant relationship between acetabular dysplasia and radiographic OA overall. Conclusions: The high prevalence of acetabular dysplasia across all grades of OA severity suggests that dysplasia itself may be an important cause of hip pain ("symptomatic adult acetabular dysplasia").